2013
DOI: 10.4314/jab.v63i1.87248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation de la qualité technologique et organoleptique de la viande de bovins de races Borgou, Lagunaire et Zébu Peulh, élevés sur des pâturages naturels

Abstract: Objectif : La qualité de la viande prend en compte la qualité technologique, la qualité organoleptique, la qualité nutritionnelle et la qualité hygiénique. Le but de cette étude est d'évaluer les qualités technologiques et organoleptiques de la viande de bovins de races Borgou, Lagunaire et Zébu Peulh, élevés sur pâturage naturels. Méthodologie et résultat : Des données ont été collectées de février à mars 2012 sur 10 Lagunaire, 10 Borgou et 10 Zébu Peulh. Les Zébu Peulh ont une température de refroidissement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The higher pH of the CDS was probably due to the coating ingredients used (Table 6). The pH values recorded in this study are similar to that obtained by Salifou et al (2013). Boubacar, Harouna, et al (2019) also observed similar pH values on market kilichi from Niger.…”
Section: Influence Of the Unit Operations On The Physicochemical Quality Of Kilichisupporting
confidence: 91%
“…The higher pH of the CDS was probably due to the coating ingredients used (Table 6). The pH values recorded in this study are similar to that obtained by Salifou et al (2013). Boubacar, Harouna, et al (2019) also observed similar pH values on market kilichi from Niger.…”
Section: Influence Of the Unit Operations On The Physicochemical Quality Of Kilichisupporting
confidence: 91%
“…The analysis of the nutritional composition of beef showed that it has an acceptable composition because the dry matter, ash, total protein and total fat contents are within the recommended range for beef [34] [35]. Indeed, the chemical composition of beef is variable [36] [37] [38].…”
Section: Discussionmentioning
confidence: 99%